Contribution to the knowledge of the Prioninae (Coleoptera, Cerambycidae) from the Mizoram State (India), with the first report of the genus Megobaralipton Lepesme & Breuning and new records from the country - Majumder, Amitava; Drumont, Alain; Jákl, Stanislav; Tavakilian, Gérard; Manjunatha, Hasaholalu Boregowda; Chandra, Kailash (Zootaxa, 2021)
Five species of Prioninae from the Indian state of Mizoram were studied: Megobaralipton kalimantanum (Komiya & Makihara, 2001); Nepiodes bowringi (Gahan, 1894); Anomophysis hainana (Gressitt, 1940); Eurypoda (Eurypoda) nigrita Thomson, 1865 and Eurypoda (Neoprion) batesi Gahan, 1894. New country records are provided to: Megobaralipton kalimantanum (Komiya & Makihara, 2001); Anomophysis hainana (Gressitt, 1940); Eurypoda (Eurypoda) nigrita Thomson, 1865; Eurypoda (Neoprion) batesi Gahan, 1894. Nepiodes bowringi (Gahan, 1894) is record for the first time from the Indian state of Mizoram. Detailed taxonomic position of all species, their host plant, and images of dorsal habitus are provided.